A common thread between the past and the present - Lyu Zhou (The UNESCO Courier, 2023)
I began my professional career in World Heritage research and conservation in 2002. I was invited by the State Administration of Cultural Heritage of China to conduct the assessment, for the Periodic Report, of the sites of Mount Taishan; the Temple and Cemetery of Confucius and the Kong Family Mansion in Qufu; and the Ancient Building Complex in the Wudang Mountains (inscribed on the World Heritage List in 1987 for the former and in 1994 for the latter two). Local authorities in China were very eager to inscribe their heritage sites on the World Heritage List back then, and we were thus under a lot of pressure. Concepts such as heritage routes, cultural landscapes and 20th century heritage were all still relatively new for China’s cultural relic protection field.